Population-Based Cohort of Children With Parapneumonic Effusion and Empyema Managed With Low Rates of Pleural Drainage - Moral, Luis; Toral, Teresa; Clavijo, Agustín; Caballero, María; Canals, Francisco; Forniés, María José; Moral, Jorge; Revert, Raquel; Lucas, Raquel; Huertas, Ana María; González, María Cristina; García-Avilés, Belén; et al. (Frontiers in Pediatrics, 2021)
Introduction: The most appropriate treatment for parapneumonic effusion (PPE), including empyema, is controversial. We analyzed the experience of our center and the hospitals in its reference area after adopting a more conservative approach that reduced the use of chest tube pleural drainage (CTPD). Methods: Review of the clinical documentation of all PPE patients in nine hospitals from 2010 to 2018. Results: A total of 318 episodes of PPE were reviewed; 157 had a thickness of less than 10 mm. The remaining 161 were 10 mm or thicker and were subdivided into three increasing sizes: PE+1, PE+2 and PE+3. There was a strong relationship between the size of the effusion and complicated effusion/empyema, defined by its appearance on imaging studies or by the physical or bacteriological characteristics of the pleural fluid. The size of effusion was also strongly related to the duration of fever and intravenous treatment and was the best independent predictor of the length of hospital stay (LHS) (p <0.001). CTPD was placed in 2.9% of PE+1 patients, 19.3% of PE+2 and 63.9% of PE+3 (p <0.001). The referral of patients with PE+1 decreased over time (p = 0.033), as did the use of CTPD in the combined PE+1/PE+2 group (p = 0.018), without affecting LHS (p = 0.814). There were no changes in the use of CTPD in the PE+3 group (p = 0.721). Conclusions: The size of the PPE is strongly correlated with its severity and with LHS. Most patients can be treated with antibiotics alone.